Mechanisms underlying childhood exposure to blue spaces and adult subjective well-being: An 18-country analysis. (December 2022) - Vitale, Valeria; Martin, Leanne; White, Mathew P.; Elliott, Lewis R.; Wyles, Kayleigh J.; Browning, Matthew H.E.M.; Pahl, Sabine; Stehl, Patricia; Bell, Simon; Bratman, Gregory N.; Gascon, Mireia; Grellier, James; et al.
Abstract: Contact with natural environments is associated with good health and well-being. Although childhood nature experiences may be important in the development of an individual's relationship with nature and subsequent well-being, previous studies have tended to focus on 'nature' in general, and the mechanisms by which childhood experiences influence well-being in adulthood remain insufficiently studied. Drawing on cross-sectional survey data from an 18-country sample (N = 15, 743) the current work extended previous research by examining: a) blue spaces (coasts, rivers, lakes, etc.) in particular; b) associations between adults' recalled childhood exposure to blue spaces, frequency of recent visits to green and blues spaces, and adult subjective well-being; c) the role of childhood exposure to blue spaces on intrinsic motivations to spend time in nature; and d) the consistency of these relationships across different countries. Tests of a model where childhood exposure to blue spaces was linked to adult subjective well-being serially through intrinsic motivation and then recent blue and green space visits exhibited a good fit, a pattern largely consistent across all 18 countries. However, an alternative model where recent visits predicted intrinsic motivation also demonstrated good fit, indicating that these processes may be iterative. Building familiarity with and confidence in and around blue spaces in childhood may stimulate a joy of, and greater propensity to spend recreational time in, nature in adulthood, with positive consequences for adult subjective well-being. Highlights: Examined the links between childhood exposure to blue spaces and adult well-being. Four alternative conceptual models were tested using data from 18 countries. Childhood exposure to blue spaces was associated with better adult well-being. The association was mediated by intrinsic motivations and recent nature visits. The pattern of associations was consistent in direction across countries.